EVALUASI TINGKAT KESEHATAN BANK DAN POTENSI FINANCIAL DISTRESS (STUDI EMPIRIS PADA BANK UMUM SYARIAH DI INDONESIA) - NADA NISRINA; SUSI RETNA CAHYANINGTYAS (Universitas Mahasaraswati K. Mataram, 2024)
This research was conducted at Sharia Commercial Banks from 2019-2022. The purpose of this study is to determine the level of bank health using the RGEC method and the potential for financial distress using the Atlman Z-Score Modified, Springate, Zmijewski, Bankometer, and Grover models. This research is a descriptive research using a quantitative approach. The results of the study on measuring the health level of banks show that from 2019-2022 based on the average value, banks are in the predicate of Quite Healthy. The results of the study on the measurement of potential financial distress show that from 2019-2022 based on the average score, the Altman Z-Score Modified, Springate, Zmijewski, Bankometer, and Grover models tend not to have the potential to experience financial distress. The results of the study on the comparison of bank health levels using the RGEC method with the potential for financial distress using the Altman Z-Score Modified, Springate, Zmijewski, Bankometer, and Grover models show that banks that have a composite rating of 4 or are in the predicate of Less Healthy do not necessarily mean experiencing financial distress.